PENGARUH EMPLOYEE WELL BEING DAN MOTIVASI KERJA TERHADAP KINERJA DIMEDIASI KEPUASAN KERJA - Hendy Nur Fatturachmad; Lie Liana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of employee well-being and work motivation on performance-mediated job satisfaction. This study uses a quantitative approach with a population of 121 civil servants of the Central Java Provincial Regional Development Planning Agency. The data was processed using SPSS software version 29. Data analysis techniques include respondent description, variable description, validity test, reliability test, F test, R2 test, t test, and Sobel test. The results of the study stated that employee well being has a positive effect on job satisfaction, work motivation has a positive effect on job satisfaction, employee well being has no effect on performance, work motivation has a positive effect on performance, job satisfaction has a positive effect on performance, job satisfaction mediates the effect of employee well-being on performance, and job satisfaction mediates the influence of work motivation on performance.